Characteristics of Head Teachers in Management of School Facilities in Kenya - John M. Mbunde; Jackson M. Njage-Rwito (European Scientific Journal, ESJ, 2018)
This paper discusses the characteristics of head teachers in management of school facilities in Kenya. The objective was: to determine the characteristics of head teachers in management of school facilities. The research employed descriptive survey design. The research instrument used was a questionnaire. Descriptive statistics technique was used to analyze the data. Then the data was presented in tables. Conclusions: Age is an important factor in school administration as it influences the authority and experiences of the head teacher; higher levels of education correlate with levels of productivity; qualification and experience enhance the head teachers’ expert power, credibility, confidence and decisiveness in managerial practice; head teachers’ administration and experience play a pivotal role in determining their attitudes and approaches as well as their problem solving techniques in their schools and participation in in-service training makes head teachers more effective and efficient in management. Recommendations: The Kenya Education Management Institute should organize in-service training programmes targeting head teachers’ management; the Ministry of Education, Science and Technology should provide adequate funding to enable the head teachers to participate in the in-service training programmes; also the ministry should reinforce the existing policies laws and enactments to enhance gender equity and the head teachers should be encouraged to continue upgrading their education level and professional qualification to enhance their knowledge, skills, attitudes and competencies in management and head teachers need to have Masters level expertise if they are to lead their schools and help their teachers become fully proficient.